2016
DOI: 10.3390/su8090907
|View full text |Cite
|
Sign up to set email alerts
|

Various Energy-Saving Approaches to a TFT-LCD Panel Fab

Abstract: This study employs the developed simulation software for the energy use of the high-tech fabrication plant (hereafter referred as a fab) to examine six energy-saving approaches for the make-up air unit (MAU) of a TFT-LCD (thin-film transistor liquid-crystal display) fab. The studied approaches include: (1) Approach 1: adjust the set point of dry bulb temperature and relative humidity in the cleanroom; (2) Approach 2: lower the flow rate of supply air volume in the MAU; (3) Approach 3: use a draw-through type i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The ECF calculator developed in the present study was further applied to comprehensively analyze results from the literature [18,20,21], including the semiconductor manufacturing and LCD fabs, of which reported data are summarized in Table 4. Our recent study reported the energy contributions of the facilities/tools of the studied LCD fab [1], as showed in Fig. 1, whereas those of other two semiconductor fabs were not available in the literature.…”
Section: Applications and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ECF calculator developed in the present study was further applied to comprehensively analyze results from the literature [18,20,21], including the semiconductor manufacturing and LCD fabs, of which reported data are summarized in Table 4. Our recent study reported the energy contributions of the facilities/tools of the studied LCD fab [1], as showed in Fig. 1, whereas those of other two semiconductor fabs were not available in the literature.…”
Section: Applications and Discussionmentioning
confidence: 99%
“…High-tech fabrication plants (fabs) generally use a lot of energy, for example, yearly energy consumption might reach 215 GWh for a 3.5 generation small/medium-size TFT-LCD (thin-film transistor liquid-crystal display) panel fab with a monthly yield of 75,000 pieces and a cleanroom area of 59,760 m 2 [1]. In addition, as reported by Williams et al [2], the energy required to convert raw silicon into a semiconductor chip is 160 times that required to produce the raw silicon, which is then used as a raw material for chip manufacture.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, Chang et al [32] investigated six strategies for controlling a cleanroom HVAC system, indicating the energy-optimal variant. They proved that the setting of the required room temperature is of key importance here; increasing this temperature by 1 • C resulted in a reduction of energy consumption by 1%.…”
Section: Introductionmentioning
confidence: 99%